Optimalisasi Peran Mediator dalam Penyelesaian Sengketa Perdata di Wilayah Pengadilan Agama Sumatera Barat - Habib Ferian Fajar; Julfahmi Syahputra (CV Rewang Rencang, 2023)
The existence of mediation in settlement of civil cases in court is regulated by the Decision of the Supreme Court of the Republic of Indonesia Number 1 of 2016 concerning Mediation Procedures in Courts. Mediation as an Alternative Dispute Resolution (ADR) is considered a humane and fair way to resolve disputes through a win-win solution stage. However, mediation is currently considered ineffective because it is only a formality, causing a low success rate of mediation in civil cases within the Religious Courts. The results of this study indicate that the implementation of mediation in the religious court environment in West Sumatra is expected to run optimally and have high success.